2013
DOI: 10.1071/fp13082
|View full text |Cite
|
Sign up to set email alerts
|

Heat-stress-induced reproductive failures in chickpea (Cicer arietinum) are associated with impaired sucrose metabolism in leaves and anthers

Abstract: Chickpea (Cicer arietinum L.), in its reproductive stage, is sensitive to heat stress (32/20°C or higher as day/night temperatures) with consequent substantial loss of potential yields at high temperatures. The physiological mechanisms associated with reproductive failures have not been established: they constitute the basis of this study. Here, we initially screened a large core-collection of chickpea against heat stress and identified two heat-tolerant (ICC15614, ICCV. 92944) and two heat-sensitive (ICC10685… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
238
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 206 publications
(277 citation statements)
references
References 67 publications
21
238
1
1
Order By: Relevance
“…The reduction in pod set as a result of heat stress in LS plants in our study is similar to observations in soybean (Djanaguiraman et al, 2013), chickpea (Kaushal et al, 2013), and mungbean (Kaur et al, 2015). The restricted availability and transport of sucrose have been implicated in reduced pod numbers in heat-stressed plants (Kaur et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…The reduction in pod set as a result of heat stress in LS plants in our study is similar to observations in soybean (Djanaguiraman et al, 2013), chickpea (Kaushal et al, 2013), and mungbean (Kaur et al, 2015). The restricted availability and transport of sucrose have been implicated in reduced pod numbers in heat-stressed plants (Kaur et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, high temperature resulted in drastic reduction in sucrose in WS-6 (Fig. 6b), which might limit the reproductive function and seed development [41,42]. The activities of starch metabolizing enzymes were affected in both wucai genotypes by heat stress, but remarkable differences were found in WS-1 and WS-6 (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Of the elevated metabolites within our heat-tolerant genotypes, most have been previously reported. Fructose and sucrose have been shown to be involved in heatstress response within tomato (Sato et al 2006) and chickpea (Kaushal et al 2013), with each declining when plants were subjected to heat stress. Similar to our results on the floral buds, Firon et al (2006) demonstrated that pollen collected from tomato plants under high temperatures exhibited different sugar concentrations depending upon sensitivity to heat, with the more tolerant genotypes maintaining a higher sugar content within the anther wall than the susceptible genotypes.…”
Section: Discussionmentioning
confidence: 99%